2018
DOI: 10.5194/essd-10-609-2018
|View full text |Cite
|
Sign up to set email alerts
|

The Ocean Carbon States Database: a proof-of-concept application of cluster analysis in the ocean carbon cycle

Abstract: Abstract. In this paper, we present a database of the basic regimes of the carbon cycle in the ocean, the “ocean carbon states”, as obtained using a data mining/pattern recognition technique in observation-based as well as model data. The goal of this study is to establish a new data analysis methodology, test it and assess its utility in providing more insights into the regional and temporal variability of the marine carbon cycle. This is important as advanced data mining techniques are becoming widely used i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Light profiles from the atmospheric radiation module are propagated underwater into the ocean and spectrally decomposed to 33 wavebands that are used to compute growth of the phytoplankton groups (Gregg et al, 2003). Latto and Romanou (2018) showed that ocean carbon states estimated from the GISS ModelE2.1 with CMIP5 carbon cycle agreed well with observations, and that study led to the current improvements in the carbon cycle simulations.…”
Section: Journal Of Advances In Modeling Earth Systemsmentioning
confidence: 84%
“…Light profiles from the atmospheric radiation module are propagated underwater into the ocean and spectrally decomposed to 33 wavebands that are used to compute growth of the phytoplankton groups (Gregg et al, 2003). Latto and Romanou (2018) showed that ocean carbon states estimated from the GISS ModelE2.1 with CMIP5 carbon cycle agreed well with observations, and that study led to the current improvements in the carbon cycle simulations.…”
Section: Journal Of Advances In Modeling Earth Systemsmentioning
confidence: 84%
“…There is parallel development of ModelE coupled to HYCOM (Sun & Bleck, 2006), where 'R' and 'G' are replaced by 'H'. The suffix 'CC' refers to an interactive carbon cycle (Romanou et al, 2013(Romanou et al, , 2014Latto & Romanou, 2018;Ito et al, 2020;Lerner et al, 2020). The domain of GISS-E2.2 extends into the mesosphere and has a better stratospheric circulation (Rind et al, 2020;Orbe et al, 2020), while GISS-E3 incorporates a new cubed-sphere grid and improved model physics.…”
Section: Models and Experimentsmentioning
confidence: 99%
“…The dominant drivers of the seasonal cycle of pCO 2, sw are those associated with the largest right‐hand side terms. Similar methods based on Taylor series expansions have been used to assess drivers in the variability of pCO 2, sw and the CO 2 flux (Doney et al., 2009; Latto & Romanou, 2018; Lovenduski et al., 2007; Mogollón & Calil, 2018). Offline calculations of pCO 2, sw are performed using the OMIP‐BGC carbonate chemistry protocols, which estimate pCO 2, sw from normalCnormalO2* (the sum of carbonic acid and dissolved CO 2 ) and the solubility of CO 2 by (i) calculating the solubility of CO 2 as a function of temperature and salinity (as for the CO 2 flux), and (ii) calculating normalCnormalO2* from pH and DIC, where pH is obtained by solving the pH‐alkalinity equation with the SolveSaphe algorithm (Munhoven, 2013; Orr et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The dominant drivers of the seasonal LERNER ET AL. (Doney et al, 2009;Latto & Romanou, 2018;Lovenduski et al, 2007;Mogollón & Calil, 2018 CO from pH and DIC, where pH is obtained by solving the pH-alkalinity equation with the SolveSaphe algorithm (Munhoven, 2013;Orr et al, 2017).…”
Section: Drivers Of Seasonal Pcomentioning
confidence: 99%
See 1 more Smart Citation